The origins of religious violence : an Asian perspective - Gier, Nicholas F., 1944- (Lexington Books, 2014)
A scholar of world religions investigates religiously motivated violence that occurred in medieval Tibet and Bhutan, as well as in modern India, Sri Lanka, Burma, and Japan. The fusion of religious and national identity in high lamas and divine kings has caused just as much violence in Asia as it did in Europe and the Middle East.